ANALYSIS OF LIMESTONE QUALITY AS THE MAIN RAW MATERIAL FOR CEMENT PRODUCTION AT PT INDOCEMENT TUNGGAL PRAKARSA TBK. PALIMANAN DISTRICT CIREBON REGENCY WEST JAVA PROVINCE - Jumryatin; Isjudarto, Agustinus; Mycelia Paradise; Partama Misdiyanta; Mustapa Ali Mohamad (ReTII, 2025)
There are high and low limestone contents found in the limestone quarry at PT Indocement Tunggal Prakarsa. Therefore, to obtain good quality raw materials, it is necessary to carry out a geochemical analysis using X-Ray Diffraction (XRD) and X-Ray Fluorescence (XRF) methods to determine the elemental content contained in the limestone, with the aim of identifying the chemical composition of each limestone sample that will be used for cement production. Based on the research and data analysis conducted, it was concluded that the lithology of rock samples 1 to 15 varies, namely samples 1, 6, 9, and 10 are mudstone, samples 2, 3, 11, and 13 are packstone, samples 5, 12, 14, and 15 are wackestone, and samples 4, 7, and 8 are boundstone. The limestone samples 9 and 1 have low CaO, SiO₂, and Al₂O₃ contents; therefore, it is recommended to perform blending of limestone that meets the required standard composition, where for CaO content of 29.93%, blending between samples 9 and 14 resulted in 62.75%; for CaO content of 47.45%, blending between samples 1 and 14 resulted in 64.51%; for SiO₂ content of 24.1%, blending between samples 1 and 12 resulted in 12.95%; for SiO₂ content of 49.09%, blending between samples 9 and 12 resulted in 15.45%; and for Al₂O₃ content of 18.04%, blending between samples 9 and 8 resulted in 5.87%. Samples 2, 4, and 12 belong to Portland Cement Type I; samples 3 and 11 belong to Portland Cement Type III; samples 3, 5, 7, and 14 belong to Portland Cement Type IV; and samples 13 and 10 belong to Portland Cement Type V. Sample 6, based on its results, can be classified into three types: Portland Cement Type I, III, and V; sample 9 can be classified into two types: Portland Cement Type IV and V; and sample 1 can be classified into two types: Portland Cement Type I and III.